2014
DOI: 10.1097/qad.0000000000000306
|View full text |Cite
|
Sign up to set email alerts
|

HIV DNA in CD14+ reservoirs is associated with regional brain atrophy in patients naive to combination antiretroviral therapy

Abstract: Objective To examine associations between regional brain volumes and HIV DNA in peripheral CD14+ cells (monocytes) among HIV-infected individuals naïve to combination antiretroviral therapy (cART). Design A prospective study of HIV-infected Thai individuals who met Thai national criteria for cART initiation. Enrollment was stratified by HIV DNA in a blinded fashion. Methods CD14+ cells were isolated from peripheral mononuclear cells to high purity (median 91.4% monocytes by flow cytometry), and HIV DNA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
(34 reference statements)
1
21
0
Order By: Relevance
“…The more robust findings for sCD163 as compared to sCD14 suggests that the impact is more likely due to specific monocyte infection than gut microbial translocation. This is consistent with prior studies linking HIV DNA in CD14 + reservoirs to cognition, brain atrophy, and brain inflammation through cytokine analyses and magnetic resonance spectroscopy [40,41]. This study also informs clinical practice in cases where successfully treated patients achieve viral suppression yet have cognitive symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…The more robust findings for sCD163 as compared to sCD14 suggests that the impact is more likely due to specific monocyte infection than gut microbial translocation. This is consistent with prior studies linking HIV DNA in CD14 + reservoirs to cognition, brain atrophy, and brain inflammation through cytokine analyses and magnetic resonance spectroscopy [40,41]. This study also informs clinical practice in cases where successfully treated patients achieve viral suppression yet have cognitive symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…Our cross-sectional analyses confirm limited volumetric reductions in HIV-infected participants with cognitive impairment compared to healthy controls, including regions previously noted to be affected in the setting of HIV, such as the cerebellum, nucleus accumbens and brainstem. 3638 These findings were driven by HIV-infected participants with HAND and we did not identify differences by HIV serostatus alone. Among the HIV infected group, the baseline volume of the nucleus accumbens and its association to executive functioning is notable.…”
Section: Discussionmentioning
confidence: 68%
“…With cART, VL usually decreases and thus it may be necessary to establish the reliability of other clinical markers of HAND. Recent work in this cohort also identified that HIV DNA reservoir levels in circulating CD14+ cells (enriched with monocytes) correlate with cognitive diagnosis and brain atrophy, specifically in the nucleus accumbens, brainstem, and total gray matter (Kallianpur, et al, 2014). …”
Section: Discussionmentioning
confidence: 77%
“…More recent MRS studies reveal elevations in metabolites suggestive of cellular inflammation during acute HIV infection (Valcour et al, 2012; Sailasuta et al, 2012) that resolved after early cART (Sailasuta et al, 2012). A separate Thai neuroimaging study reported reduced regional brain volumes in cART naïve HIV+ individuals who had higher levels of peripheral HIV DNA compared to HIV+ individuals with lower HIV DNA levels (Kallianpur, 2014). However, prior studies did not characterize HIV+ by HAND status or compare brain volumes in HIV+ individuals, with and without HAND to HIV− uninfected individuals in Thailand.…”
mentioning
confidence: 99%